The Moderating Effect of Islamic Organizational Culture on the Association of Servant Leadership, Perceived Organizational Support and Team Performance in Palestinian Organizations - Abuhayya, Montaser (Arab Journal for Sciences and Research Publishing, 2017)
The purpose of this study is to investigate the fundamental factors of Servant Leadership and Perceived organizational Support and their influence on Team Performance. Moreover, the study identifies the role of Islamic organizational Culture and its impact on Team Performance among Palestinian employees in the business sector. In addition, this study ascertains how incorporating the Contingency Theory of Leadership and organizational Support Theory is pertinent to developing nations with divergent degrees of explanatory power. These theories are used to examine the factors of Team Performance among Palestinian employees from companies whose leaders are members of the Palestinian Businessmen Association. The sample for the present study consisted of 220 participants and used Structural Equation Modelling in order to analyse the causal relationships among the study’s latent variables. The indirect exploratory effect of the moderators was examined using Multiple-Group Analysis (MGA). The results of the study indicate that Servant Leadership and Perceived organizational Support have a significant and positive effect on Team Performance among Palestinian employees. Furthermore, the study’s findings demonstrate that organizational Support is a partial mediator between Servant Leadership and Team Performance. Furthermore, the findings of the study reveal that Islamic organizational Culture has a moderating effect on Team Performance. The research study also discusses previous empirical findings and its practical applications and implications for the Palestinian context.
Keywords: Servant Leadership; Team Performance; Perceived organizational Support; Islamic organizational Culture